Randomized comparison of the clinical outcome of single versus multiple arterial grafts: the ROMA trial—rationale and study protocol - Gaudino, Mario; Alexander, John H; Bakaeen, Faisal G; Ballman, Karla; Barili, Fabio; Calafiore, Antonio Maria; Davierwala, Piroze; Goldman, Steven; Kappetein, Peter; Lorusso, Roberto; Mylotte, Darren; Pagano, Domenico; et al. (European journal of cardio-thoracic surgery, 2017)
SUMMARY The primary hypothesis of the ROMA trial is that in patients undergoing primary isolated non-emergent coronary artery bypass grafting, the use of 2 or more arterial grafts compared with a single arterial graft (SAG) is associated with a reduction in the composite outcome of death from any cause, any stroke, post-discharge myocardial infarction and/or repeat revascularization. The secondary hypothesis is that in these patients, the use of 2 or more arterial grafts compared with a SAG is associated with improved survival. The ROMA trial is a prospective, unblinded, randomized event-driven multicentre trial comprising at least 4300 subjects. Patients younger than 70 years with left main and/or multivessel disease will be randomized to a SAG or multiple arterial grafts to the left coronary system in a 1:1 fashion. Permuted block randomization stratified by the centre and the type of second arterial graft will be used. The primary outcome will be a composite of death from any cause, any stroke, post-discharge myocardial infarction and/or repeat revascularization. The secondary outcome will be all-cause mortality. The primary safety outcome will be a composite of death from any cause, any stroke and any myocardial infarction. In all patients, 1 internal thoracic artery will be anastomosed to the left anterior descending coronary artery. For patients randomized to the SAG group, saphenous vein grafts will be used for all non-left anterior descending target vessels. For patients randomized to the multiple arterial graft group, the main target vessel of the lateral wall will be grafted with either a radial artery or a second internal thoracic artery. Additional grafts for the multiple arterial graft group can be saphenous veins or supplemental arterial conduits. To detect a 20% relative reduction in the primary outcome, with 90% power at 5% alpha and assuming a time-to-event analysis, the sample size must include 845 events (and 3650 patients). To detect a 20% relative reduction in the secondary outcome, with 80% power at 5% alpha, the sample size must include 631 events (and 3650 patients). To be conservative, the sample size will be set at 4300 patients. The primary outcome will be tested according to the intention-to-treat principle. The primary analysis will be a Cox proportional hazards regression model, with the treatment arm included as a covariate. If non-proportional hazards are observed, alternatives to Cox proportional hazards regression will be explored.